IMPLEMENTATION OF MAUT METHOD GRANTING BUSINESS LICENSES IN TANJUNGBALAI CITY - Tanya Raisita; Hambali Hambali; Cecep Maulana (STMIK Royal, 2024)
Abstract: Establishing a business or industrial location must obtain permission from the government which aims to protect the surrounding community from possible disturbances or pollution resulting from the industry. Therefore, in order to achieve this, it is necessary to have a system that automatically provides accurate and fast decisions in determining which companies or industries are worthy of being granted a business license. The aim of this research is to build a decision support system in determining permits to disturb business or industrial premises using the Multi-Attribute Utility Theory (MAUT) method. The data analysis technique used is the MAUT method to determine the final decision in granting a disturbance permit to a company or industry. The sample or training data consists of 20 names in the Tanjungbalai City area. This system is tested with a black box which aims to find out that all components in the system are running well. Our findings show that the system we have created is appropriate based on the results of the analysis using the MAUT method. Apart from that, the results of black box testing show that all components in this system are valid and functioning well.Keywords: granting business licenses; maut method; web based. Abstrak: Mendirikan tempat usaha atau industri harus mendapatkan izin dari pemerintah yang bertujuan untuk melindungi masyarakat sekitar agar terlindungi dari kemungkinan timbulnya gangguan atau polusi yang diakibatkan dari industry tersebut. Oleh karena itu, demi tercapainya hal tersebut perlu adanya sistem yang secara otomatis memberikan keputusan secara akurat dan cepat dalam menentukan suatu perusahaan atau industry mana yang layak diberikan izin usaha. Tujuan penelitian ini adalah untuk membangun sistem pendukung keputusan dalam menentukan izin gangguan tempat usaha atau industri menggunakan metode Multi-Attribute Utility Theory (MAUT). Teknik analisis data yang digunakan menggunakan metode MAUT untuk menentukan keputusan akhir dalam memberikan izin gangguan kepada perusahaan atau industri. Sampel atau data training yang berjumlah 20 nama di wilayah Kota Tanjungbalai. Sistem ini diuji dengan black box yang bertujuan untuk mengetahui semua komponen pada sistem sudah berjalan dengan baik. Hasil penelitian menunjukkan bahwa sistem yang telah kami buat sudah sesuai berdasarkan hasil analisis menggunakan metode MAUT. Selain itu, hasil black box testing menunjukkan bahwa semua komponen pada sistem ini sudah valid dan berfungsi dengan baik.Kata kunci: berbasis web; metode maut; pemberian izin usaha.